2004
DOI: 10.2308/accr.2004.79.4.967
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Equity and Earnings Attributes

Abstract: We examine the relation between the cost of equity capital and seven attributes of earnings: accrual quality, persistence, predictability, smoothness, value relevance, timeliness, and conservatism. We characterize the first four attributes as accounting-based because they are typically measured using accounting information only. We characterize the last three attributes as market-based because proxies for these constructs are typically based on relations between market data and accounting data. Based on theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

98
1,709
18
180

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,987 publications
(2,005 citation statements)
references
References 56 publications
98
1,709
18
180
Order By: Relevance
“…A persistência também possui uma ligação direta com o risco da informação, porque mais persistência está associada a um fluxo de ganhos mais sustentável. Como consequência, se os ganhos são persistentes, os investidores demonstram menos preocupações sobre a extensão em que as alterações nos ganhos dos períodos futuros poderão ocorrer, e isso reduz incertezas (FRANCIS et al, 2004).Os lucros atuais devem ser um bom indicador dos lucros futuros. Sua qualidade pode ser entendida como a probabilidade de que uma empresa possa ter lucros atuais persistentes no futuro ZHANG, 2002).…”
unclassified
See 3 more Smart Citations
“…A persistência também possui uma ligação direta com o risco da informação, porque mais persistência está associada a um fluxo de ganhos mais sustentável. Como consequência, se os ganhos são persistentes, os investidores demonstram menos preocupações sobre a extensão em que as alterações nos ganhos dos períodos futuros poderão ocorrer, e isso reduz incertezas (FRANCIS et al, 2004).Os lucros atuais devem ser um bom indicador dos lucros futuros. Sua qualidade pode ser entendida como a probabilidade de que uma empresa possa ter lucros atuais persistentes no futuro ZHANG, 2002).…”
unclassified
“…Sua qualidade pode ser entendida como a probabilidade de que uma empresa possa ter lucros atuais persistentes no futuro ZHANG, 2002). Mais persistência dos ganhos é considerada uma característica de qualidade superior de contabilidade (KOHLBECK; WARFIELD, 2010).A previsibilidade dos lucros é definida como a habilidade de prever lucros futuros com base nos seus valores do passado (LIPE, 1990;FRANCIS et al, 2004;YOON, 2007). Isso é uma medida importante, uma vez que lida com o quão bem os lucros passados podem explicar os lucros atuais.…”
unclassified
See 2 more Smart Citations
“…There are always some reasons to have different numbers between actual and formal statements such as lack of good prediction for future events, applying different accounting methods, etc. Several empirical studies indicated that poor earnings quality could lead to increase in information risk and eventually it could increase the cost of equity (Francis et al, 2004). Since profit is the most important components of business evaluation, quality of earning has become the most important subject of research for the past few years.…”
Section: Introductionmentioning
confidence: 99%